Diversity of Medicinal Plants in the Flora of Saudi Arabia 3: An inventory of 15 Plant Families and their Conservation Management - Yusuf, Mohammed; Al-Oqail, Mai M; Al-Sheddr, Ebtesam S; Al-Rehaily, Adnan Jathlan; Rahman, M Atiqur (International Journal of Environment, 2014)
An inventory of medicinal species diversity in the flora of the Kingdom of Saudi Arabia has been made for 15 angiosperm families, viz., Boraginaceae, Convolvulaceae, Cucurbitaceae, Fabaceae, Molluginaceae, Papavaraceae, Portulacaceae, Ranunculaceae, Rhamnaceae, Rutaceae, Tamaricaceae, Tiliaceae, Urticaceae, Verbenaceae and Vitaceae, and 61 species of medicinal plants are recognized. These families are represented in the flora by a total of 393 species of which 15.52% are medicinal. Among the families, the Fabaceae is found to be represented by 23 medicinal species which is highest and 37.70% of the total species. Of these 61 medicinal species, 72.13% exhibits herbaceous life form while remaining 13.11% and 14.75% exhibit shrubs and trees respectively. An enumeration of these medicinal species is presented, each with current nomenclature, Arabic name, English name, medicinal uses, pharmacological properties and status of occurrence in the flora. The communication is aimed at emphasizing the planning and implementation of national conservation strategies for sustainable management of the medicinal plants of the Kingdom of Saudi Arabia. DOI: http://dx.doi.org/10.3126/ije.v3i3.11091 International Journal of Environment Vol.3(3) 2014: 312-320